Muscle Growth and Distribution in Fattening Steer of Different Breeds - R Priyanto; E R Johnson (Media Peternakan, 2011)
The breed patterns in growth and distribution of muscle were studied using three breeds of beef cattle entering fattening phase. This study involved 23 grass-fed steer Brahman, 24 Hereford and 22 Brahman x Hereford crosses with a live weight range of 300 to 600 kgs. An allometric Huxley model was used to study the growth and distribution patterns of muscle tissue within wholesale cut.  There were several cuts in which the muscle growth coefficients were significantly different among breeds. Comparisons of muscle weight distribution at log natural of 75 kg side muscle + bone weight (4.313 kg) generally showed significant between-breed differences. Herefords tended to have more muscles in their wholesale cuts than Brahmans and/or Brahman x Hereford crosses, except the muscles in Tenderloin, Rib Set and Chuck. Brahmans had heavier Topside and Silverside than Herefords and Brahman x Hereford crosses and the differences were maintained at log natural of 114 kg side muscle + bone weight (4.733 kg).  At this heavier weight, there was a general tendency for Brahmans to have more muscle in their wholesale cuts than the Brahman x Hereford steers, except the muscle in Loin and Neck + Sticking.